Selenium accumulation by plants - White, Philip J. (Annals of botany, 2016)
Selenium (Se) is an essential mineral element for animals and humans, which they acquire largely from plants. The Se concentration in edible plants is determined by the Se phytoavailability in soils. Selenium is not an essential element for plants, but excessive Se can be toxic. Thus, soil Se phytoavailability determines the ecology of plants. Most plants cannot grow on seleniferous soils. Most plants that grow on seleniferous soils accumulate <100 mg Se kg(-1) dry matter and cannot tolerate greater tissue Se concentrations. However, some plant species have evolved tolerance to Se, and commonly accumulate tissue Se concentrations >100 mg Se kg(-1) dry matter. These plants are considered to be Se accumulators. Some species can even accumulate Se concentrations of 1000-15 000 mg Se kg(-1 )dry matter and are called Se hyperaccumulators. This article provides an overview of Se uptake, translocation and metabolism in plants and highlights the possible genetic basis of differences in these between and within plant species. The review focuses initially on adaptations allowing plants to tolerate large Se concentrations in their tissues and the evolutionary origin of species that hyperaccumulate Se. It then describes the variation in tissue Se concentrations between and within angiosperm species and identifies genes encoding enzymes limiting the rates of incorporation of Se into organic compounds and chromosomal loci that might enable the development of crops with greater Se concentrations in their edible portions. Finally, it discusses transgenic approaches enabling plants to tolerate greater Se concentrations in the rhizosphere and in their tissues. The trait of Se hyperaccumulation has evolved several times in separate angiosperm clades. The ability to tolerate large tissue Se concentrations is primarily related to the ability to divert Se away from the accumulation of selenocysteine and selenomethionine, which might be incorporated into non-functional proteins, through the synthesis of less toxic Se metabilites. There is potential to breed or select crops with greater Se concentrations in their edible tissues, which might be used to increase dietary Se intakes of animals and humans.